2016
DOI: 10.1007/s11156-016-0612-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of firm ownership, board monitoring on operating performance of Chinese mergers and acquisitions

Abstract: In this paper, we employ board monitoring mechanisms and within-firm governance variables to investigate the operating performance of 340 mergers and acquisitions (M&A) in China over the 2004-2011 period. Our results document a significant deterioration in post-acquisition operating performance of acquiring firms over 12-36 months. We find independent directors, managerial shareholding, ownership concentration have a positive and significant impact on operating performance of acquiring firms. However, the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 112 publications
2
15
0
Order By: Relevance
“…The results indicate that related-party transactions enjoy a more positive CSR effect on long-term M&A performance than those with non-related party transactions. Our findings are contradicted by some studies, which concluded CSR leads to a "Resource Hollowing" effect [9,[51][52][53][54]. However, our findings are consistent with studies which concluded CSR brings about an "Efficiency Enhancing" effect [11][12][13].…”
Section: Effects Of Related-party Transactions On Csr-performance Linsupporting
confidence: 50%
See 2 more Smart Citations
“…The results indicate that related-party transactions enjoy a more positive CSR effect on long-term M&A performance than those with non-related party transactions. Our findings are contradicted by some studies, which concluded CSR leads to a "Resource Hollowing" effect [9,[51][52][53][54]. However, our findings are consistent with studies which concluded CSR brings about an "Efficiency Enhancing" effect [11][12][13].…”
Section: Effects Of Related-party Transactions On Csr-performance Linsupporting
confidence: 50%
“…With respect to M&A activities, there are also negative effects of related-party transactions. For example, Boateng et al (2017) [54] found that an acquiring firm's operating performance significantly deteriorates after the acquisition. However, good governance has a significantly positive effect on the acquiring firm's performance.…”
Section: Csr Related-party Transactions and Long-term Manda Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (2015) [20] demonstrate that equity financing can effectively improve M&A performance, and that its impact will be affected by ownership type and level of national financial development. In their examination of M&A transactions among Chinese A-share listed companies from 2009 to 2011, Boateng et al (2017) [23] consider that there is no "inaction" among SOEs after M&A. On the contrary, M&A performance is significantly better than that of POEs because they can obtain abundant resources and financial support from the government that is conducive to M&A integration.…”
Section: Manda Financing Ownership and Manda Performancementioning
confidence: 99%
“…Unlike a majority of Western-based studies that highlight the positive effects of debt financing on ensuing firm performance, it provides new evidence that in a rapidly developing economy with unique legal requirements and institutional environments, China, equity-financed M&A transactions lead to significantly better performance than debt-financed transactions. Second, in terms of research perspectives, different from the recent studies on China that highlight the beneficial role the Chinese government has had in value creation through facilitating M&A deals [2,23,24], the impact of ownership on M&A payment methods, and the impact of payment methods on stock price returns [22], we examine the joint effects of both financing methods and ownership on M&A financial performance. This is important because both financing choices and ownership will affect the competitiveness, resourcing, costs and effective functioning of acquirers.…”
Section: Introductionmentioning
confidence: 99%